Estimating the value of risk reduction for pedestrians in the road environment: An exploratory analysis - David A. Hensher; John M. Rose; Juan de Dios Ortúzar; Luis I. Rizzi (Journal of Choice Modelling, 2011)
In recent years there has been a re-focus on the valuation of a statistical life from the ex post or human capital method to an ex ante willingness to pay (WTP) approach. This is in part a recognition that we need to focus on establishing the amount, ex ante, that individuals are willing to pay to reduce the risk of exposure to circumstances that might lead to death or degree of injury in the road environment. This study sets out a framework in which to identify the degree of preference heterogeneity in WTP of pedestrians to avoid being killed or injured. A stated choice experiment approach is developed. The empirical setting is a choice of walking route for a particular trip that a sample of pedestrians periodically undertakes in Australia. Mixed logit models are estimated to obtain the marginal (dis)utilities associated with each influence on the choice amongst the attribute packages offered in the stated choice scenarios. These conditional estimates are used to obtain the WTP distributions for fatality and classes of injury avoidance, which are then aggregated to obtain estimates for pedestrians of the value of risk reduction (VRR).
Keywords: 330; value of statistical life; value of risk reduction; fatalities; serious injury; pedestrians; choice experiment; willingness to pay; survey; Australia